DIGITAL TRANSFORMATION OF URBAN TRANSPORT SYSTEMS: CLASSIFICATION OF APPROACHES AND RECOMMENDATIONS FOR UKRAINE - POSTRELKO, YEVHENII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article explores modern approaches to the digital transformation of urban transport systems, emphasizing their classification, implementation examples in Ukraine and abroad, and the development of an adaptive model tailored for Ukrainian cities. Against the backdrop of growing urbanization and increased pressure on transport infrastructure, traditional management methods often prove ineffective. In response, many cities are adopting innovative strategies that integrate infrastructure upgrades, organizational reforms, and digital technologies. The article presents a three-part classification of urban mobility approaches: infrastructural solutions (such as lane prioritization and automated traffic control), organizational strategies (including schedule optimization and multimodal integration), and digital tools (such as real-time monitoring and visualization platforms). This framework provides a foundation for systematic comparison and evaluation of various transport policies and interventions. Using case studies from Lviv, Kyiv, Vinnytsia, Dnipro, as well as international examples like Helsinki and Barcelona, the article highlights key factors that determine the success or limitations of these implementations. It outlines a scalable, stepwise model for Ukrainian cities, including a basic level focused on data transparency, a mid-level involving service optimization, and an advanced level enabling predictive analytics and adaptive transport management. Additionally, the article proposes practical criteria for evaluating the effectiveness of implemented systems and emphasizes the importance of collaboration among local governments, IT companies, and research institutions. The study offers an evidence-based roadmap for urban policymakers aiming to modernize transport systems in a sustainable, resource-aware manner.
Keywords: web system; public transport monitoring; urban transport; mobility as a service; urban mobility